2006
DOI: 10.1002/hep.21415
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hepatocellular carcinoma recurrence with alpha-interferon after liver resection in HCV cirrhosis

Abstract: . The primary end point was recurrence-free survival (RFS); secondary end points were disease-specific and overall survival. Intention-to-treat and subgroup analysis on adherent patients were conducted. Treatment effects on early/late recurrences were assessed using multiple Cox regression analysis. No patient experienced life-threatening adverse events. There were 28 adherent patients (37%). After 45 months of median follow-up, overall survival was 58.5%, and no significant difference in RFS was detectable be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
316
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(336 citation statements)
references
References 44 publications
8
316
2
3
Order By: Relevance
“…Another RCT in Italy did not detect effects of IFN therapy on early recurrence but late recurrence, with more than 2 years of interval, seemed to be reduced among IFN responders [403]. These data are compatible with the hypothesis that de novo carcinogenesis was prevented by successful antiviral therapy.…”
Section: Tertiary Prevention Of Hcv-related Hccsupporting
confidence: 61%
“…Another RCT in Italy did not detect effects of IFN therapy on early recurrence but late recurrence, with more than 2 years of interval, seemed to be reduced among IFN responders [403]. These data are compatible with the hypothesis that de novo carcinogenesis was prevented by successful antiviral therapy.…”
Section: Tertiary Prevention Of Hcv-related Hccsupporting
confidence: 61%
“…[18][19][20] In light of the effects of adjuvant IFN therapy on HCC recurrence after surgical resection, it has been suggested that adjuvant IFN therapy may reduce late recurrences after surgery or prolong the disease-free survival, although this has not been validated statistically in a general study population. 4,21 Taken together, we believe that these findings deserve a careful re-evaluation to determine whether adjuvant IFN therapy may prevent or retard HCC recurrence in a particular subgroup that has a very high risk of recurrence. Thus, the objective of the current study was to investigate whether postoperative, adjuvant pegylated-IFN (Peg-IFN) therapy can reduce the rate of recurrence after curative surgical resection in patients with MTA1-positive HCC who are at high risk of recurrence.…”
Section: Introductionmentioning
confidence: 83%
“…IFN has been studied as adjuvant therapy after liver resection or ablation of HCC in HCV infected cirrhotics because of its anti-carcinogenic properties (89)(90)(91)(92)(93)(94)(95). Among 209 patients with HCV who underwent curative resection for HCC, 70 patients underwent IFN therapy (89).…”
Section: Ifn After Liver Resection or Ablation To Prevent Or Treat Rementioning
confidence: 99%